Study on influencing factors and prevention measures of coal-rock-gas compound dynamic disaster in deep coal mine mining - Xu Wang; Chenglin Tian; Qingbiao Wang; Zhenyue Shi; Yong Sun; Keyong Wang (Scientific Reports)
Abstract Because coal seam mining with high geostress and high gas pressure is prone to coal–rock–gas compound dynamic disasters, a disaster energy equation considering the influence of roof elastic energy is established, and a disaster energy criterion considering the influence of roof elastic energy is derived and introduced into COMSOL software to conduct numerical simulations of coal seam mining under different geostress and gas pressures. The study revealed that the increase of ground stress reduces the gas pressure required for disaster occurrence. When the gas pressure reaches a certain value, the disaster will occur even if the ground stress is very small. When the ground stress and gas pressure are very low, by changing the magnitude of ground stress or gas pressure, outburst, rockburst and coal‒rock‒gas composite dynamic disasters can transform into each other. As the depth of the excavated coal seam increases, the geostress‒gas pressure increases from 15‒0.5 MPa to 20‒0.74 MPa and 25‒1 MPa, the peak stress and peak gas pressure can reach maximum values of 39.61 MPa and 1.11 MPa, respectively, the difference between the elastic energy of the coal rock body and the expansion energy of the gas is not large, and the energy criterion is greater than 1 and increasing, which indicates that the occurrence of a compound dynamic disaster and the degree of hazard gradually increase. The high-pressure water jet slit technology can increase the average gas extraction volume by 3.6 times, the peak stress is transferred from 7 m away from the coal wall to 10 m, and the peak stress is transferred to the deep coal wall, which can effectively reduce the stress in the coal rock mass and the gas pressure in the coal seam.